Children born of genocidal rape: What do we know about their experiences and needs?. Issue 1 (8th December 2021) - Uwizeye, Glorieuse; DeVon, Holli A.; McCreary, Linda L.; Patil, Crystal L.; Thayer, Zaneta M.; Rutherford, Julienne N.
Abstract: Background: An often under addressed and tragic legacy of genocide is the conception of children from rape. While the experience has been documented from their mothers' perspective, the perspectives and needs of individuals born of genocidal rape has been under‐studied. Methods: We conducted an integrative review of all peer‐reviewed articles that reported on studies conducted among individuals born of genocidal rape published through 2020. We used an inductive process to identify and describe the themes from those studies. Results: Twelve studies met the inclusion criteria. Ten articles reported on youth born of genocidal rape in Rwanda aged between 16 and 21 years, and two articles represented the perspective of adolescents in the former Yugoslavia aged 1416 years. Four themes were indentified: (1) birth origin stories associated with the crime of the father, (2) fractured sense of belonging to the victim‐mother, perpetrator‐father, their families, and the community at large, (3) intergenerational legacy of trauma and family identity, and (4) strategies to move forward including knowing the truth about one's origin, mental health, and peer support. Conclusion: These findings suggest that understanding increased risk of adverse health outcomes of youth born of genocidal rape could inform the design of evidence‐based interventions for these and similar populations.